Giant isolated profunda femoris artery aneurysm treated with aneurysmal ligation without profunda femoris artery revascularization - Naveed A. Rahman, MD; Zachary E. Williams, BS; Asad Choudhry, MD; Scott Surowiec, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2023)
Isolated nonruptured profunda femoris artery (PFA) aneurysms are exceedingly rare. We present the case of an 80-year-old man who initially presented with a large pulsatile mass in the right groin. Computed tomography angiography identified a giant 6-cm PFA aneurysm. This was a truly isolated PFA aneurysm without any evidence of concomitant abdominal aortic or popliteal aneurysms. Potential surgical options included reconstruction with an interposition graft, endovascular coil embolization, and aneurysmal ligation. We elected to perform aneurysmal ligation of the PFA aneurysm without revascularization given the aneurysm's massive size and patency of the superficial femoral artery.